(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In article national images in O.O.Suleymenov’s creativity are analyzed. O. Suleymenov’s many-sided creativity doesn’t need representations for the Kazakhstan readers. In Suleymenov’s verses constantly there lives thought of the homeland, the great interest to people life is felt. The poet with love describes traditions, customs, characters. All heroes of its works – proud people with high moral who are in love with life. In spite of the fact that O. Suleymenov is the Russian-speaking poet, his creativity – property of all Kazakh people. Most of all the poet appreciates those phenomena of human spirit which bear in itself humanistic spirit of good, help the person to be exempted from prejudices, false belief and deceptive hopes. But the main thing that grants to us the right to call this or that work by the phenomenon of national art is a completeness of reflection of national reality in all its historical concreteness and right prospect, penetration into an essence, complexity of national, national character.